LINC00887 promotes GCN5-dependent H3K27cr level and CRC metastasis via recruitment of YEATS2 and enhancing ETS1 expression - Meijian Liao; Wendan Zheng; Yifan Wang; Mengting Li; Xiaolin Sun; Nan Liu; Jia Yao; Fuxing Dong; Qingling Wang; Yu Ma; Jie Mou (Cell Death and Disease, 2024)
Abstract Recent observations have revealed upregulation of H3K27cr in colorectal cancer (CRC) tissues; however, the underlying cause remains elusive. This study aimed to investigate the mechanism of H3K27cr upregulation and its roles in CRC metastasis. Clinically, our findings showed that H3K27cr served as a highly accurate diagnostic marker to distinguish CRC tissues from healthy controls. Elevated levels of LINC00887 and H3K27cr were associated with a poorer prognosis in CRC patients. Functionally, LINC00887 and H3K27cr facilitated the migration and invasion of CRC cells. Mechanistically, LINC00887 interacted with SIRT3 protein. Overexpressed of LINC00887 obstructed the enrichment of SIRT3 within GCN5 promoter, thereby elevating H3K27ac but not H3K27cr level within this region, subsequently activating GCN5 expression. This activation increased the global level of H3K27cr, promoting the enrichment of GCN5, H3K27cr, and YEATS2 within ETS1 promoter, activating ETS1 transcription and ultimately promoting the metastasis of CRC. The in vivo study demonstrated that inhibition of LINC00887 suppressed CRC metastasis, but this inhibitory effect was nullified when mice were treated with NaCr. In conclusion, our results confirmed the diagnostic biomarker potential of H3K27cr in individuals with CRC, and proposed a functional model to elucidate the involvement of LINC00887 in promoting CRC metastasis by elevating H3K27cr level.